Civil War Almanac - Segal, Justin (Los Angeles Lowell House Juvenile, 1997)
This almanac brings to life the excitement and the devastation of this pivotal War between the States. You will also find historic photos, as well as a section on additional sources books, movies, CD-ROMs, and Websites to help you understand and explore the Civil War even further!
Keywords: History